Desenvolvimento e avaliação in vitro de complexo de inclusão carvacrol: hidroxipropil-βciclodextrina sobre Rhipicephalus microplus (Acari: Ixodidae) - Assunção, Gabriela Rocha de (2021)
Rhipicephalus microplus is responsible for significant damage to cattle farming worldwide and the control of this parasite has encountered barriers, such as resistance to ticks. Carvacrol (CAR) is a potential alternative acaricide, however, due to characteristics such as volatility and low dispersibility in water, its application in the field has been difficult. In order to minimize these characteristics, the objective of this work was to prepare and characterize the effect of the inclusion complex (CI) containing CAR and hydroxypropyl-β-cyclodextrin (HP-βCD) on R. microplus tick larvae. The CI CAR:HP-βCD was prepared by the kneading method and its formation was confirmed by thermogravimetric analysis, Infrared spectroscopy and Nuclear Magnetic Resonance (NMR). By analyzing the DTG graph for the IC, no evidence of the presence of free CAR was observed. This result may be related to the increase in stability of the CAR due to the formation of the CI. From the spectra of free and complexed CAR, obtained by 1H NMR, a variation in chemical shifts for aromatic hydrogens was observed, suggesting the inclusion of CAR in the HP-βCD cavity. In the ROESY 2D spectrum of the CI, an interaction between the aromatic protons of the CAR and the HP-βCD cavity was also observed, showing that the carvacrol molecule is capable of being incorporated into the HP-βCD cavity. The acaricidal effect of CI was evaluated using the larval pack test, which, when solubilized in 5% (m v-1 ) of DMSO, showed a larvicidal effect (LC90 9.6 mg/mL) and increased time of action of carvacrol, with larval mortality of 99.69% after 30h, when compared to free carvacrol, which showed larval mortality of 68.25% after the same period. Thus, the formation of CI CAR:HP-βCD through the kneading technique, provided protection of the active compound, decreased volatility, ensuring activity for a longer time.